Hydrological transitions: a story of Kansas watershed districts - Jean, Christy Roberts (Kansas State University, 2016)
Kansas watershed projects have been responsible for reducing floodwater damage across the state since the formation of watershed districts, following the Kansas Watershed District Act of 1953. A total of 80 organized watershed districts now take on the responsibilities associated with watershed management and protecting the land uses within them. Today, Kansas watershed districts face challenges in completing nearly half of the 3,000 structures proposed since 1953. Insufficient funding, burdensome policy changes, and a declining interest from local board members and landowners are key challenges boards must overcome in addition to managing rapidly aging infrastructure and dealing with projects that have exceeded their life expectancy. Research methods used for this report include content analysis of general work plans, relevant federal and state policies, and interviews with local stakeholders. In order to understand the economic, political, social and geographic impacts of watershed development, the following issues are addressed: cost-benefit ratios using monetary and non-monetary benefits, differences between federal and state funding in regards to rehabilitation and best management practices, local perceptions of watershed development, and spatial factors that exist among watershed districts. This study found that watershed projects have the potential to provide up to $115 million each year in monetary and flood damage reduction benefits in Kansas protecting over 35,000 miles of transportation routes while providing recreation opportunities and enhancing environmental conservation efforts. Political and social impacts were identified through in-person interviews with 21 local stakeholders that include landowners, board members and state representatives, representing 21 different watershed districts. Perceptions of political and social issues indicate that when government assistance is available, watershed districts are more willing to deal with increased regulations. However, a lack of financial support that has existed in Kansas watershed districts over the last eight years has contributed to a general opposition of increased federal regulations and reluctance to continue building watershed structures. Spatial factors among watershed districts illustrate the spatial and temporal differences in district development, watershed structure construction, and precipitation gradients that influence land use and ecoregions between western and eastern Kansas.
Keywords: Watershed management; Watersheds; Kansas watershed districts; Sociohydrology; Geography (0366)